Detachment of CVD-grown graphene from single crystalline Ni films by a pure gas phase reaction - Zeller, Patrick; Henß, Ann-Kathrin; Weinl, Michael; Diehl, Leo; Keefer, Daniel; Lippmann, Judith; Schulz, Anne; Kraus, Jürgen; Schreck, Matthias; Wintterlin, Joost (Surface science, 2016)
Despite great previous efforts there is still a high need for a simple, clean, and upscalable method for detaching epitaxial graphene from the metal support on which it was grown. We present a method based on a pure gas phase reaction that is free of solvents and polymer supports and avoids mechanical transfer steps. The graphene was grown on 150nm thick, single crystalline Ni(111) films on Si(111) wafers with YSZ buffer layers. Its quality was monitored by using low energy electron diffraction and scanning tunneling microscopy. The gas phase etching uses a chemical transport reaction, the so-called Mond process, based on the formation of gaseous nickel tetracarbonyl in ~1bar of CO at ~75°C and by adding small amounts of sulfide catalysts. X-ray photoelectron spectroscopy, Raman spectroscopy and scanning electron microscopy were used to characterize the detached graphene. It was found that the method successfully removes the nickel from underneath the graphene layer, so that the graphene lies on the insulating oxide buffer layer. Small residual particles of nickel sulfide and cracks in the obtained graphene layer were identified. The defect concentrations were comparable to graphene samples obtained by wet chemical etching and by the bubbling transfer. [Display omitted] •Graphene was grown on a single crystal Ni(111) film supported on a YSZ-buffered Si(111) support.•The Ni film was removed by a pure gas phase reaction under mild conditions.•The reaction uses a transport reaction based on the formation of gaseous nickel tetra carbonyl.•Afterwards the graphene layer lies on the insulating support without mechanical transfer step.